Analisis Penggunaan Teknologi Big Data Dalam Analisis Risiko Bisnis - Dyandra Sastra Wardani; Edi Saputra; Felita Jekri; Mutia Putri Dewi Apriyanti; Handoko Handoko; Yarzan Munakalla (Politeknik Raflesia Press, 2025)
The aim of this research is to find out how big data technology is used in business risk analysis. The use of big data today is very massive, used in many fields including accounting or economics. The need for data in a business is important for business people to carry out operations and make decisions and create policies to enable the business they own to reduce risks that may occur. The research method used in this research is a qualitative method with a library approach. Based on research conducted, it was found that Big data can be used to identify and stop dangers in the financial industry.